2023
DOI: 10.2106/jbjs.oa.22.00112
|View full text |Cite
|
Sign up to set email alerts
|

Projections and Epidemiology of Primary Hip and Knee Arthroplasty in Medicare Patients to 2040-2060

Abstract: Background:National projections of future joint arthroplasties are useful for understanding the changing burden of surgery and related outcomes on the health system. The aim of this study is to update the literature by producing Medicare projections for primary total joint arthroplasty (TJA) procedures until 2040 and 2060.Methods:The present study used data from the Centers for Medicare & Medicaid Services (CMS) Medicare/Medicaid Part B National Summary and combined procedure counts with use of Current Procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 16 publications
0
50
1
Order By: Relevance
“…Knee Surg Relat Res. 2023 Apr 27;35 (1): 12. This retrospective study aimed to assess the advantages of performing UKA on a single indicated side in patients undergoing simultaneous bilateral knee arthroplasty. The study compared 33 cases of simultaneous bilateral UKA and TKA with 99 cases of simultaneous bilateral TKA.…”
Section: Evidence-based Orthopaedicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knee Surg Relat Res. 2023 Apr 27;35 (1): 12. This retrospective study aimed to assess the advantages of performing UKA on a single indicated side in patients undergoing simultaneous bilateral knee arthroplasty. The study compared 33 cases of simultaneous bilateral UKA and TKA with 99 cases of simultaneous bilateral TKA.…”
Section: Evidence-based Orthopaedicsmentioning
confidence: 99%
“…In addition to the articles cited already in this update, 9 other articles relevant to adult reconstructive knee surgery are appended to this review after the standard bibliography, with a brief commentary about each article to help guide your further reading, in an evidencebased fashion, in this subspecialty area. Jesus M. Villa, MD 1 Shayan Hosseinzadeh, MD 1 Carlos A. Higuera-Rueda, MD 1 1 Levitetz Department of Orthopaedic Surgery, Cleveland Clinic Florida, Weston, Florida Email for corresponding author: higuerc@ccf.org…”
Section: Evidence-based Orthopaedicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total joint arthroplasty (TJA) is considered one of the most successful surgical innovations of the 20th century, thanks to its proved efficacy in relieving pain and improving function in a durable and cost‐effective manner when appropriately indicated [1, 40, 63]. The volume of these procedures has risen dramatically over the past several decades, with over 800,000 total hip and knee arthroplasties being performed annually in the United States only [17, 24, 32, 72]. Moreover, a further increase is expected with 1.22 million prostheses foreseen by 2040 in the United States [72].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of these procedures has risen dramatically over the past several decades, with over 800,000 total hip and knee arthroplasties being performed annually in the United States only [17, 24, 32, 72]. Moreover, a further increase is expected with 1.22 million prostheses foreseen by 2040 in the United States [72]. This implies important consequences for the healthcare systems [61, 72].…”
Section: Introductionmentioning
confidence: 99%